HIDE probes: A new toolkit for visualizing organelle dynamics, longer and at super-resolution - Thompson, Alexander D. (Biochemistry, 2017)
Living cells are complex and dynamic assemblies that carefully sequester and orchestrate multiple diverse processes that enable growth, division, regulation, movement, and communication. Membrane-bound organelles such as the endoplasmic reticulum, mitochondria, plasma membrane, and others are integral to these processes and their functions demand dynamic reorganization in both space and time. Visualizing these dynamics in live cells over long time periods demands probes that label discrete organelles specifically, at high density, and withstand long-term irradiation. Here we describe the evolution of our work on the development of a set of High Density Environmentally sensitive (HIDE) membrane probes that enable long-term, live-cell nanoscopy of the dynamics of multiple organelles in live cells using SMS and STED imaging modalities.